The System of Mythological Characters in the Turkic Epic: The Karachay-Balkarian Nartiada and Yakut Olonkho - Semen S. Makarov; Tanzila M. Khadzhieva (Studia Litterarum)
The article explores the parallels in the structure of character systems of the Karachay-Balkarian version of the Nartiada and Yakut heroic epos Olonkho. The main focus is on the typical attributes and plot functions of such groups of characters as celestial demiurges and protectors of epic heroes and their demonic antagonists. The research aims to assess the degree of typological proximity of the studied traditions based on the analysis of one of the levels of the system of epic characters. The article reveals the close connection of the plots of the Karachay-Balkarian Nartiada and the Yakut epic Olonkho with the ritual and mythological context. In both traditions, a similar circle of characters in structure and functions is revealed — the patrons of the hero, attributed as deities (тейри, айыы таҥара) and also represented in the real religious and mythological practice of the bearers of traditions. Noticeable coincidences in the plots of the Karachay-Balkarian and Yakut epics are also found in the field of demonological conceptions. They have such common features as the chthonic kind and monstrous appearance of the antagonists of the hero, the presence in the plots of an expressive image of the mother of epic demons. These features stem from the general typological properties of the archaic heroic epic. At the same time, such features as the serpentomorphism of the chthonic demoness and the ‘landscape’ semantics of tropes applied to antagonists can be considered as genetically related elements, possibly dating back to the proto-Turkic mythological worldview.